2009
DOI: 10.1016/s0828-282x(09)70139-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional health status of adolescents after the Fontan procedure – comparison with their siblings

Abstract: Adolescents with Fontan physiology reported a lower functional health status in physical domains than their siblings, but had similar status in psychosocial domains. Having a sibling was associated with lower reported functional health status, suggesting an important effect of self-perceived physical limitations over true limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…Significantly better scores were found in all CHQ domains (except self-esteem) in 306 teens with repair of transposition of the great arteries compared with norms for those without health problems (Culbert et al, 2003). No differences were found between child and parent scores on the PedsQL (Manlhiot et al, 2009).…”
Section: Qol Of Individuals With Chdmentioning
confidence: 74%
See 2 more Smart Citations
“…Significantly better scores were found in all CHQ domains (except self-esteem) in 306 teens with repair of transposition of the great arteries compared with norms for those without health problems (Culbert et al, 2003). No differences were found between child and parent scores on the PedsQL (Manlhiot et al, 2009).…”
Section: Qol Of Individuals With Chdmentioning
confidence: 74%
“…In three studies, adolescents with mild, moderate, and severe CHD reported significantly lower QoL compared with peers without CHD (Krol et al, 2003;Manlhiot et al, 2009;Spijkerboer et al, 2006). Another study found that only teens with severe heart disease, and not those with mild or moderate heart disease, had significantly lower QoL compared with those without CHDs (Cohen et al, 2007).…”
Section: Qol Of Individuals With Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Ongoing studies of HRQOL, as patients who have undergone the Fontan procedure age and develop Fontan failure, will be important to guide interventions. Patients with Fontan physiology also report higher levels of depression than healthy controls.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Physical functional status and physical quality-of-life measures have been shown to be reduced compared with healthy control populations 10 11. Furthermore, data from the ongoing Single Ventricle Trial group have very clearly shown poorer neurodevelopment as measured by the psychomotor development index, motor development index of the Bayley development scores at 14 months 12 13…”
Section: Introductionmentioning
confidence: 99%